(untitled) (SAARC Journal of Agriculture, 2021)
To minimize the production cost of poultry and poultry products, it is important to formulate low cost balanced ration utilizing unconventional feed resources. Therefore, the experiment was carried out to measure the effect of substituting soybean meal (SBM) by different levels of shrimp head meal (SHM) to the ration of growing layer pullets. A control corn-soybean layer grower (pullet) diet and four different levels of SHM included diets as substitution of SBMwere fed to five groups of Hisex White pullets from 5th to 18th weeks of age. All groups of pullets fed isocaloric feeds (2765 Kcal kg-1). The control group T0 (0 % SHM+20 % SBM) received grower ration formulated with traditional feed ingredients with no substitution of SBM. The SBM contents of other treatment groups were substituted at the rate of 25 %, 50 %, 75 % and 100 % by the SHM and were adjusted as 5 % SHM+15 % SBM (T1), 10 % SHM+10 % SBM (T2), 15 % SHM+5 % SBM (T3) and 20 % SHM+0 % SBM (T4) keeping other ingredients constant as of control. Cumulative feed intake increased with the increasing level of SHM of diets. Feed cost and mortality rate decreased with the increasing level of SHM in the ration. Significantly lowest FCR at most of the age categories, highest cumulative body weight (p<0.05) at 18 weeks and highest weight at maturity (p<0.05) were found in treatment group fed 5 % SHM. Therefore, it can be concluded that substitution of 25 % SBM of the ration by SHM is suitable for the better performance of growing layer pullets. SAARC J. Agri., 18(2): 125-137 (2020)